Transformasi bisnis menuju era industry 5.0: Peran teknologi E-commerce - Zami, Putri Adz'biya Zam (Maliki Interdisciplinary Journal, 2024)
The progress of e-commerce cannot be separated from the growth of the internet, Because e-commerce operates through network infrastructure and internet connection. The rapid growth of internet users has made the internet an effective platform for companies and individuals to introduce and sell products and services to consumers in various parts of the world. Based on the background of the problem above, the purpose of this paper is as follows: a.) Understanding How E-commerce Develops in the Era of Industry 5.0, b.) Understanding How the Readiness of Society in the Era of Industry 4.0 Welcomes the Era of Society 5.0. c.) Understanding How Efforts to Develop E-commerce in the Era of Industry 5.0. The result of this discussion is that the 5.0 industry revolution must be faced by balancing the needs and necessities of society and the country. Technological advancements everywhere must be balanced with societal advancements, so there is no overlap between local and international.